Enhancing Modern Standard Arabic Pronunciation Through Qur’anic Recitation Techniques - Djemai Mahmoud Boulaares; Abdullah Saad Alamri (Ijaz Arabi Journal of Arabic Learning, 2026)
Modern Standard Arabic (MSA) poses well-documented pronunciation challenges for adult non-native speakers due to its rich phonological system, including sounds absent in many learners’ first languages. This study investigates an innovative pedagogical approach: leveraging Qur’anic recitation techniques (Tajwīd) to enhance MSA pronunciation among non-native speakers. A quasi-experimental design was adopted in which one group of learners received traditional pronunciation training while the experimental group received supplementary Tajwīd-based instruction focusing on the precise articulation of Arabic phonemes. Pre- and post-intervention pronunciation assessments (expert ratings and acoustic analyses) indicate that the Tajwīd-trained group achieved significantly greater improvement in segmental pronunciation accuracy and clarity than the control group. Qualitative feedback also suggests heightened learner confidence and awareness of articulation. These findings highlight that integrating Qur’anic recitation rules, which emphasise exact phonetic realisation, into MSA instruction can substantially improve learners’ pronunciation. The paper discusses implications for Arabic as a foreign language pedagogy, noting that this culturally informed technique offers a promising complement to traditional methods, and recommends its incorporation to help learners attain more native-like pronunciation in MSA.